2010
DOI: 10.1063/1.3269706
|View full text |Cite
|
Sign up to set email alerts
|

Annealing temperature and initial iron valence ratio effects on the structural characteristics of nanoscale nickel zinc ferrite

Abstract: Nickel zinc ferrite ͑NZFO͒ nanoparticles were synthesized via a reverse micelle method with a nonionic surfactant. Three different initial Fe 3+ / Fe 2+ ratios were employed along with three different firing temperatures ͑200, 500, 1000°C͒ to investigate the effects on the NZFO system. Extended x-ray absorption fine structure ͑EXAFS͒ results reveal zinc loss at high annealing temperatures; at 1000°C, the loss is nearly total for Fe 3+ / Fe 2+ ratios other than 10:90. Annealing at 500°C, however, appears necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…This method suffers from disadvantages like chemical inhomogeneity, coarser particle size and impurity insertion during the process [4]. In recent years several researchers have prepared nanosized ferrites by sol-gel method [2,5], emulsion method [6], co-precipitation method [2,7], citrate precursor method [8], tartrate precursor method [9], hydrothermal method [10], reverse micelle technique [11], microemulsions [12], high energy ball milling technique [13] and pulsed wire discharge method [14]. There are many reports in literature on the studies of Ni-Cr [15], Ni-Ge [16], Ni-Zn [17,18], Ni-Al [19], Ni-Cd [20], Ni-Li [21], Ni-Cu [22], Ni-Mg [23] and Ni-Mn [24] ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…This method suffers from disadvantages like chemical inhomogeneity, coarser particle size and impurity insertion during the process [4]. In recent years several researchers have prepared nanosized ferrites by sol-gel method [2,5], emulsion method [6], co-precipitation method [2,7], citrate precursor method [8], tartrate precursor method [9], hydrothermal method [10], reverse micelle technique [11], microemulsions [12], high energy ball milling technique [13] and pulsed wire discharge method [14]. There are many reports in literature on the studies of Ni-Cr [15], Ni-Ge [16], Ni-Zn [17,18], Ni-Al [19], Ni-Cd [20], Ni-Li [21], Ni-Cu [22], Ni-Mg [23] and Ni-Mn [24] ferrites.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the cation distribution in the spinel structure could be inuenced by the particle size, the preparation method, the calcination temperature, and the cationdoping. [28][29][30][31][32] As the magnetic moments of cations located in the tetrahedral and octahedral sites couple in an antiparallel alignment, the net magnetization of the spinel ferrites is related to the difference between those of the octahedral and tetrahedral cations. 32 Accordingly, the change in the cation distribution can signicantly affect the magnetic properties of materials, e.g., saturation magnetization, coercivity and Curie temperature.…”
Section: Resultsmentioning
confidence: 99%
“…32 Accordingly, the change in the cation distribution can signicantly affect the magnetic properties of materials, e.g., saturation magnetization, coercivity and Curie temperature. 29,31 It is therefore important to gain the full structural information. The local structure and cation distribution of these CuFe 2 O 4 spinel nanoparticles were further determined by XAS analysis.…”
Section: Resultsmentioning
confidence: 99%